(3eWGdY GdCfhGQ HehdO GdfHi GdeNJGQs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CQSd eMeO Udi Gddg Ydjg hSde QMeh ddYGdejf GeG HYO agPg QSGdI dWjaI ai PcQ ehdOg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hcGf Oafg Udi Gddg Ydjg hSde djdI GdCQHYGA ef hSW GddjdI hbjd ZjQ Pdc hYGTJ HYOg GHfJg aGWeI QVi Gddg YfgG SJg CTgQ aeG VMcJ (B" (3ai Jdc GdeOI hMb dgG Pdc dCf cd eUjHI Jghf YfO gPg GdeUjHg aEfG ddg hEfG Edjg QGLYhf hdG Mhd hdG bhI EdG HGddg GdYdis
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs